“THE STYLISTIC FUNCTIONS AND TYPES OF INVERSION IN J.ORWELL`S NOVEL “1984” (KONFERENSIYA, 2025)
This study explores the use of inversion as an important stylistic element in George Orwell’s 1984, focusing on how unusual word order contributes to the novel’s meaning and narrative expression. The research identifies the main types of inversion found in the text and analyzes the specific contexts in which they appear. Attention is given to the way inverted structures highlight key ideas, strengthen emotional undertones, and reflect the tense atmosphere of a society dominated by control and surveillance. The analysis shows that Orwell employs inversion not only for emphasis but also to reveal the inner state of the characters and the ideological pressure shaping their speech. Overall, the findings suggest that inversion helps reinforce the novel’s central themes and plays a meaningful role in constructing its stylistic and thematic depth